2015
DOI: 10.4049/jimmunol.1402044
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Aryl Hydrocarbon Receptor with Altered DNA Methylation Patterns and Developmentally Induced Aberrant Antiviral CD8+ T Cell Responses

Abstract: Successfully fighting infection requires a properly tuned immune system. Recent epidemiological studies link exposure to pollutants that bind the aryl hydrocarbon receptor (AHR) during development with poorer immune responses later in life. Yet, how developmental triggering of AHR durably alters immune cell function remains unknown. Using a mouse model, we show that developmental activation of AHR leads to long-lasting reduction in the response of CD8+ T cells during influenza virus infection, cells critical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 73 publications
10
52
0
Order By: Relevance
“…During influenza virus infection, AHR deficiency impacts the primary CD8 T cell response in a cell-extrinsic manner [59]. In the absence of AHR, antigen-specific CD8 T cells display altered DNA methylation patterns and a transcriptional profile reminiscent of exhausted CD8 T cells [60]. Similarly, AHR controls retention and/or survival of tissue resident memory CD8 T cells in the skin [61].…”
Section: Ahr and T Cellsmentioning
confidence: 99%
“…During influenza virus infection, AHR deficiency impacts the primary CD8 T cell response in a cell-extrinsic manner [59]. In the absence of AHR, antigen-specific CD8 T cells display altered DNA methylation patterns and a transcriptional profile reminiscent of exhausted CD8 T cells [60]. Similarly, AHR controls retention and/or survival of tissue resident memory CD8 T cells in the skin [61].…”
Section: Ahr and T Cellsmentioning
confidence: 99%
“…Due to its functional duality between toxicity and normal physiology (Fig. 1) the AHR is uniquely positioned not only to convert signals from environmental toxicants into alterations of embryonic development, but to trigger a sustained state of cardiovascular insufficiency that increases the risk of adult disease [2, 8, 12-16]. Consonant with the postulates of the Barker Theory of the Developmental Origins of Health and Disease [17], developmental cardiac insufficiency may translate in the adult into congenital heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…IDO enzymatic activity activates the aryl-hydrocarbon receptor (AHR) [95][96][97]. Recent studies have shown that developmental activation of AHR leads to a long-lasting reduction in the response of CD8 T cells during influenza virus infection through alteration of DNA methylation and gene expression patterns which push CD8 T cells toward an "exhausted" transcriptomic program [98]. AHR and HIF1α have also been shown to control type 1 regulatory T cell differentiation [99].…”
Section: Signaling and Transcriptional Regulation In "Exhausted" T Cellsmentioning
confidence: 99%